1974
DOI: 10.1039/f19747002145
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Langmuir method for kinetic studies of decomposition reactions: calcite (CaCO3)

Abstract: The Langmuir method for measurement of vapour pressures has been tested for use in studies of decomposition reactions. The isothermal weight loss in vacuum from cleavage (1011) planes of calcite (CaC03) single crystals was measured continuously at temperatures from 934 to 1013 K. The rate was constant until approximately 80 % of a 1 mm slice had decomposed. The apparent activation enthalpy was 205 kJ (49 kcal) mol-'. Micrographic examination showed an approximately 30 pm thick layer, probably a metastable form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 1 publication
5
102
0
1
Order By: Relevance
“…Two different experimental approaches under high vacuum can be selected from numerous experimental studies of the kinetics of the thermal decomposition of calcium carbonate, as a possible solution for the kinetic analysis of reversible solid-state decompositions. One is the Langmuir method employed by Beruto and Searcy [12], in which the rate of linear advance of the reaction interface along a selected direction of a single crystalline or shaped sample is subjected to kinetic study at constant temperatures under high vacuum. The Langmuir method has several advantages [12], compared with the conventional thermogravimetry (TG) for measuring the decomposition rates for powdered or granular samples in flowing inert gas.…”
Section: Introductionmentioning
confidence: 99%
“…Two different experimental approaches under high vacuum can be selected from numerous experimental studies of the kinetics of the thermal decomposition of calcium carbonate, as a possible solution for the kinetic analysis of reversible solid-state decompositions. One is the Langmuir method employed by Beruto and Searcy [12], in which the rate of linear advance of the reaction interface along a selected direction of a single crystalline or shaped sample is subjected to kinetic study at constant temperatures under high vacuum. The Langmuir method has several advantages [12], compared with the conventional thermogravimetry (TG) for measuring the decomposition rates for powdered or granular samples in flowing inert gas.…”
Section: Introductionmentioning
confidence: 99%
“…Calcite crystals with a spectrographic analysis given in a previous paper [1] were cut along (lOll) planes to obtain slices 2 ~o. 75 mm thick, with areas of ~ 20 mm and rv40 mg weight.…”
Section: Methodsmentioning
confidence: 99%
“…distinguishable CaO layers [1,2]. Beruto and Searcy [3] suggested that the intermediate CaO layer transforms to the second CaO layer as a consequence of accumulated strain.…”
mentioning
confidence: 99%
“…Wang and Thompson [44], as well as Beruto and Searcy [45], determined the activation energy of calcite to be as high as 197 kJ/mol and 205 kJ/mol. Sceats et al [17] subsequently estimated the power that was required for the calcination reaction to being 2.6 MW for 1.45 kg mineral feed per second per calcination unit employed.…”
Section: Heat Transfermentioning
confidence: 99%